Brawler - Connelly, Neil O. (2019)
High school champion wrestler Eddie MacIntyre does not mind his well-earned reputation as a loose cannon, but when he punches a referee he not only loses his chance at the state championships, he gets expelled from school--facing the strong possibility of joining his father in prison, he runs away and joins an illegal underground fighting ring, where he and a girl fighter named Khajee find themselves trapped in a violent world, run by bad men and gamblers.
Keywords: Hand-to-hand fighting -- Juvenile fiction; Violence in sports -- Juvenile fiction; Aggressiveness -- Juvenile fiction; Organized crime -- Juvenile fiction; Gambling -- Juvenile fiction; Man-woman relationships -- Juvenile fiction; Boxing -- Fiction